Detection of Formalin in Salted Squid Using Dragon Fruit Peel Extract (Hylocereus polyrhizus) - Supriyatin; Hery Prambudi (Jurnal Penelitian Pendidikan IPA, 2025)
This research aims to determine the presence of salted squid sold at the Main Jatibarang market in Indramayu using dragon fruit peel extract, determine the level of formaldehyde in the samples and whether there is a difference when using dragon fruit peel extract and chromatophic acid in detecting formaldehyde in salted squid. The research method used in this research is descriptive comparative, while the qualitative examination method uses dragon fruit peel extract, chromatophic acid and for quantitative examination the chromatophic acid method uses a UV-Vis spectrophotometer. Data analysis uses univariate analysis in SPSS and describes the results descriptively. The results of qualitative tests or qualitative detection of formalin using dragon fruit peel extract and chromatogenic acid obtained the same results, namely 5 (five) positive samples in the same sample. Qualitative results show that there is no difference in positive results from two different methods for detecting formalin. Meanwhile, quantitative tests using a UV-Vis spectrophotometer with a wavelength of 570nm resulted in samples D1 having a concentration of 7.22ppm, D2 having a concentration of 7.25ppm, D3 having a concentration of 6.77ppm, D4 having a concentration of 6.76ppm, and D5 having a concentration of 6.72ppm.